Quality of Ancho maize populations from Guerrero, Mexico, for pozole-making - García-Cruz, Leticia (2026)
Introduction. The Ancho maize race, native to the state of Guerrero, exhibits wide variability that has been insufficiently characterized. Objective. To determine the physical and pasting properties, the quality of flowered kernel, and the content of total soluble phenols and anthocyanins in eleven populations of Ancho maize from Guerrero. Materials and methods. Collections were carried out in five municipalities of the state of Guerrero, Mexico, during the springÐsummer 2022 production cycle. Kernel physical traits were evaluated, and nixtamalization was performed using the traditional method to assess flowered grain quality. Data were analyzed through analysis of variance, followed by Tukey’s multiple comparison test (p ² 0.05). A principal component analysis was also conducted. Results. The populations exhibited wide variability in physical traits, including hundred-kernel weight (47.8Ð99.85 g), endosperm hardness (73.5Ð99 %), color, pasting properties, and phenolic content. Regarding flowered grain quality (FG), populations A67, A65, and A02 stood out for their high yields, higher flowering volume, and short cooking times. In some cases, phenolic content in FG decreased to 79.8 %. The highest retention of total soluble phenols and anthocyanins was observed in population A10Az, characterized by blue-purple kernels. Conclusions. Populations of the Ancho landrace exhibited considerable variability across all evaluated traits. Among them, populations A65, A67, and A03 stood out for their exceptional flowered quality and enhanced phenol retention.